Kerajaan Elektronik - Penerimaan Teknologi Aplikasi e-Khidmat - Mohd Azmi, Hj Omar (2009)
The purpose of this research is to investigate and observe the level of technology acceptance among users of e-Services application. e-Services application is one of the pioneer application under the establishment of electronic government. The electronic government was introduced as a part of Multimedia Super Corridor project on 1st August 1996, which is one of the key instruments of Vision 2020. In addition, this research developed based on the technology acceptance model (TAM) and containing four factors as independent variables and dependent variables, namely perceived usefulness, perceived ease of use, perceived Internet security and total amount of information. Data collected using developed questionnaires and was sent out through electronic mail (e-mail) to registered e-Services respondents. A total of 93l questionnaires were distributed, and 397 were returned, with a response rate of 43.93 percent. The research finding shows those 81.9 percent respondents have low level of acceptance of e-Services application, 16.6 percent is at medium level and the balance of 1.5 percent have high level of acceptance of e-Services application. Overall, the level of technology acceptance of e-Services application is low. The results from one-way ANOVA analysis between the age factor and level of education with technology acceptance, perceived usefulness; perceived ease of use, perceived Internet security and total amount of information revealed that there is no statistically significant differences for the age factor. However, there is statistically significant difference between education level with perceived ease of use, perceived Internet security and total amount of information. Based on Pearson Correlation analysis indicates that there exists a significant relationship between all the factors with technology acceptance of e-Services application. Moreover, multiple regression technique was employed and discovered only perceived usefulness and perceived ease of use have effect on the findings of technology acceptance of e-Services application. Finally, the research findings is discuss, identify the limitations of the study,and a few suggestions is proposed for the future directions of the research.